Evaluasi kebijakan pembangunan industri dijawa timur yang berwawasan sumber daya manusia dalam sustainability development - Agus Prianto; M. Sulhan (Publisia: Jurnal Ilmu Administrasi Publik, 2020)
In the era of industrialization, the people have problems, especially human resources, community culture, social systems, which lead to social welfare. The presence of the government in the industrial sector as a provider of employment with regulations on the development of indutrialization since 2018 the growth of industrialization has increased 14.48% which is only in the industrial sector which grew in the food manufacturing industry sector 12.35%, the metal industry 17.97%, the industry furniture 21.50% and the recording and printing industry 27.25%. Seeing the growth and not comparable with the HDI jawatimur related to labor, it needs to be compromised about strengthening the informal sector in East Java as well as the protection of workers in the informal sector both in management and regulation.DOI: 10.26905/pjiap.v5i1.3647